Introduction of Physics Application for Medical Imaging on CT Scan Modalities at SMA Efata Tangerang - Josua Timotius Manik; Eunike Winda Ayusari; Gabriella Novinda; Tumpal Pandiangan (Jurnal Pengabdian Masyarakat Bestari, 2023)
The physics contribution in medicine began with the discovery of x-rays by Wilhelm Roentgen in 1895. The uses of ionizing radiation for medical imaging applied to the CT scan modality to obtain inside images of the human body based on differences in organ density. Preliminary observations show that students at SMA Efata Tangerang do not have enough knowledge about physics and its application in medicine. Therefore, the Physics Study Program at Matana University carried out community service activities (PKM) in order to introduce medical physics to the students at SMA Efata. The PKM activities are carried out in the form of seminars which are divided into three sessions using lecture and discussion methods. The results of this service show that PKM activities can spur the motivation and interest of students at SMA Efata in studying physics.